An Analysis of the Flouting of Conversational Maxims by Grice on ‘A Clean, Well-Lighted Place’ Short Story - Listiana Ikawati (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2022)
This study aimed to analyze the use of flouted conversational maxims found in “A Clean, Well-lighted Place” short story by Ernest Hemingway. This is qualitative research with content analysis research design. The results of the study reveal two main findings. First, from the total data of 50, 27 (54%) data contain the flouted conversational maxims. The highest frequency of flouting is found in the maxim of relevance in which there are 11 data (40.74%) and 4 data (14.81%) represent the lowest frequency which is the flouting of the maxim of manner. The number of flouting in the maxim of quantity and quality is 7 (25.93%) and 5 (18.52%) respectively. Second, those maxims are flouted for certain reasons such as avoiding the speaker to be direct and impolite when talking about darkness and loneliness, being old and nothingness as the themes of the short story. By flouting the maxim of quality, the speaker tries to keep a secret. The speaker avoids responding to negative opinions or showing his disagreement by flouting the maxim of quantity. The speaker’s flouting on the maxim of quality is done to maintain the conversation and to keep a secret the speaker the maxim of manner is flouted. Thus, flouting the conversational maxims is sometimes done by the interlocutors which does not necessarily mean that they do not want to maintain the conversation, yet it is another way to avoid the conversation breakdowns. Based on the result of the research, the study implies that it is important for both interlocutors to have common belief that successful communication requires them to cooperate and maintain the communication either by adhering the conversational maxims or even flouting the maxims due to certain reasons